Estimating sensitivity and specificity of a faecal examination method for Schistosoma japonicum infection in cats, dogs, water buffaloes, pigs, and rats in western Samar and Sorsogon Provinces, The Philippines - Carabin, H.; Balolong, E.; Joseph, L; McGarvey, S.T.; Johansen, M.V.; Fernández, T.; Willingham, Arve Lee; Olveda, R. (Elsevier, 2005)
Schistosoma japonicum causes a chronic parasitic disease, which persists as a major public health concern in The Philippines, the People's Republic of China and Indonesia. This infection is unique among helminthic zoonoses because it can infect humans and more than 40 other mammals. The objective of this study was to estimate the sensitivity and specificity of the Danish Bilharziasis Laboratory technique in cats, dogs, pigs, water buffaloes and rats in the Philippines. Faecal samples from each animal were collected on up to five occasions on five consecutive days in four villages of Sorsogon and Western Samar Provinces between January and July 2003. The faecal samples were analysed with the filtration and sedimentation Danish Bilharziasis Laboratory technique. Sensitivity and specificity of one, two, three, four, and five faecal samples were estimated using a Bayesian latent class approach. A total of 59, 43, 74, and 80% of the censored cats, dogs, pigs, and water buffaloes in the four villages were sampled, respectively. For all species, the sensitivity estimates when using the results of only 1 day of sampling were less than 80%. However, the sensitivity improved to more than 96% in all species when three or more faecal samples were collected on three separate days. The specificity was estimated to be above 92% across all species, even if just a single sample is used. The prevalences and 95% credible intervals of S. japonicum, adjusted for imperfect sensitivity and specificity, in cats, dogs, pigs, rats, and water buffaloes were 11.9% (6.8–18.3%), 19.9% (15.1 and 25.2%), 2.9% (1.1 and 5.2%), 31.3% (18.3–45.6%) and 6.3% (2.1–12.6%), respectively. Our results suggest that the Danish Bilharziasis Laboratory technique is valid for the detection of infection with S. japonicum in animals, and that sensitivity estimates are excellent when faecal samples are collected on at least three different days. Monitoring S. japonicum infection in animal reservoirs with a valid test could contribute to more effective public health control programmes.